2003
DOI: 10.1088/0953-8984/15/28/369
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the preparation and characterization of transuranium systems

Abstract: The most remarkable advance that one can report as regards transuranium systems is certainly the discovery of superconductivity above 18 K in PuCoGa5. Motivated by this discovery, we have investigated bulk samples of both PuCoGa5 and its Rh analogue. Characterizations of polycrystalline Co and Rh compounds are reported. The new PuRhGa5 compound is also found to become superconducting above 8 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
164
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(166 citation statements)
references
References 5 publications
2
164
0
Order By: Relevance
“…Superconductivity is also found in PuRhGa 5 at T c = 8.7 K, which has a slightly smaller Sommerfeld coefficient ␥ ϳ 50 mJ/ mol K 2 . 9 In contrast, no superconductivity or magnetic order is observed in PuIrGa 5 down to 1.4 K. 29 As in the case of the UMGa 5 materials, the largest relative increase in hybridization is found in V fd in PuMGa 5 , consistent with the decrease in Sommerfeld coefficient; extension of this model to PuIrGa 5 indicates an even smaller ␥ for this compound, in agreement with the small value of the T 2 coefficient of the electrical resistivity. 29,33 One might expect that V fd may play a role in determining T c , which varies by a factor of 2 between PuCoGa 5 and PuRhGa 5 ; however, it has recently been shown that structural tuning plays a more important role in the superconductivity of both PuMGa 5 and the heavy-fermion CeMIn 5 ͑M =Co,Rh,Ir͒ compounds.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Superconductivity is also found in PuRhGa 5 at T c = 8.7 K, which has a slightly smaller Sommerfeld coefficient ␥ ϳ 50 mJ/ mol K 2 . 9 In contrast, no superconductivity or magnetic order is observed in PuIrGa 5 down to 1.4 K. 29 As in the case of the UMGa 5 materials, the largest relative increase in hybridization is found in V fd in PuMGa 5 , consistent with the decrease in Sommerfeld coefficient; extension of this model to PuIrGa 5 indicates an even smaller ␥ for this compound, in agreement with the small value of the T 2 coefficient of the electrical resistivity. 29,33 One might expect that V fd may play a role in determining T c , which varies by a factor of 2 between PuCoGa 5 and PuRhGa 5 ; however, it has recently been shown that structural tuning plays a more important role in the superconductivity of both PuMGa 5 and the heavy-fermion CeMIn 5 ͑M =Co,Rh,Ir͒ compounds.…”
Section: Discussionmentioning
confidence: 74%
“…[4][5][6][7] Quite recently, superconductivity has also been reported in isostructural PuCoGa 5 and PuRhGa 5 . 8,9 Although less is known about these plutonium-based materials, the underlying physics appears to be similar 10 to that of CeMIn 5 and, in particular, seems to rely on the existence of at least partially localized f electrons. [11][12][13] A family of uranium-based analogues of CeMIn 5 and PuMGa 5 was reported some time ago.…”
Section: Introductionmentioning
confidence: 99%
“…82,86,87,88,89,90 Tanaka et al 91 used periodic Anderson model to describe d-wave superconducting state of PuCoGa 5 . Its isostructural counterpart PuRhGa 5 shows analogous properties but with the lower value of SC transition temperature T c = 8 K. 92 PuCoGa 5 crystallizes in tetragonal P 4/mmm space group with a = 4.232Å and c = 6.782Å. 82 Electronic structure calculation of PuCoGa 5 was performed in fully relativistic full-potential method of local orbitals.…”
Section: B Pucoga5mentioning
confidence: 99%
“…4 Recent experimental discovery of the isostructural superconductors PuTX 5 (T = Co and Rh, X = Ga and In) with the tetragonal HoCoGa 5 -type structure has stimulated those discussions. [5][6][7][8] Actinide elements and their compounds have accordingly been extensively studied despite their attendant experimental difficulties.…”
Section: Introductionmentioning
confidence: 99%